Dandelion (Taraxacum officinale): A Promising Source of Nutritional and Therapeutic Compounds - Laila, Umi; Kaur, Jaspreet; Sharma, Kartik; Singh, Jyoti; Rasane, Prasad; Kaur, Sawinder; Bhadariya, Vishesh (Recent Advances in Food Nutrition & Agriculture, 2025)
BackgroundTaraxacum officinale, commonly referred to as dandelion, is a self-growing plant/ weed in various parts of India and the rest of the world (particularly the northern hemisphere). The plant’s chemical composition, including sesquiterpene lactones, saponins, flavonoids, phenols, and many other compounds, contributes positively to the human body, promoting overall health.AimThis review aims to shed light on the therapeutic potential of dandelion by summarizing its nutritional benefits, phytochemical constituents, and effectiveness in addressing health conditions like diabetes, inflammation, and cancer. It also provides insights into the applications of this plant beyond the food industry to gain researchers' attention to unravel the unexplored aspects of this therapeutic plant. It will further help in laying specific considerations, which are required to be taken into account before the development of functional foods incorporated with dandelion.Scope and approachBeing rich in essential vitamins, minerals, and other phytoconstituents, dandelion is a natural remedy for various ailments. Whether consumed raw or cooked, the plant’s inclusion in the diet poses potential therapeutic effects on conditions such as diabetes, inflammation, liver disease, and tumors. It also aids in immune system modulation and fights infections by targeting microbes at their root. Researchers have developed various value-added food products by incorporating different parts of dandelion.ConclusionThis review highlights the therapeutic potential of dandelion, emphasizing its effectiveness against various health conditions. Insights into dosage, toxicity, and diverse applications further underscore its role as a versatile and promising natural remedy.
Keywords: pharmacological properties